2022
DOI: 10.1039/d2na00359g
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble GaAsSb/GaAs axial configured nanowire-based separate absorption, charge, and multiplication avalanche near-infrared photodetectors

Abstract: In this study, molecular beam epitaxially grown axially configured ensemble GaAsSb/GaAs separate absorption, charge, and multiplication (SACM) region-based nanowire avalanche photodetector device on non-patterned Si substrate is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Next, the following material and device characterizations were chosen to comprehensively consider the influence of various growth processes on the morphological and optical quality of p-i-n NW heterostructure and their cumulative impact on the device operation, similar to our previous work in this area [12,25,31,32]. NW morphology and composition were assessed using the energy dispersive x-ray spectroscopy integrated to Carl-Zeiss Auriga field emission scanning electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Next, the following material and device characterizations were chosen to comprehensively consider the influence of various growth processes on the morphological and optical quality of p-i-n NW heterostructure and their cumulative impact on the device operation, similar to our previous work in this area [12,25,31,32]. NW morphology and composition were assessed using the energy dispersive x-ray spectroscopy integrated to Carl-Zeiss Auriga field emission scanning electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…While the observed gain and spectral sensing are significant, the observed V BR is much higher than that reported in the literature in vertical ensemble NW APDs. 1,24,27 Further decrease in device dark current and device consistency features is possible via pattered growth of these heterostructures. Since the growth mechanism of the NWs is non-selective, axial variation in the thickness of individual growth segments can be pronounced due to the shadowing effect, 53 along with thickness disparity among the NWs.…”
Section: S10t and H30mentioning
confidence: 99%
“…A work on GaAs CS nanoneedle APDs by Chuang et al 24 showcases high avalanche multiplication at RT at a significantly lower breakdown voltage. Parakh et al 27 recently demonstrated an axially configured ensemble of NW APDs, with a low breakdown voltage and significant gain exceeding 200 at RT on an arsenide-antimonide system. It is evident that most of the prior work is dedicated to arsenide material systems, with no reports on antimonide material systems in the CS NW configuration despite its promising application wavelength range in the NIR region.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, the unique advantage of NW-SPAD is that low dark count rate performance can be maintained despite operating near room temperature, thanks to its nanoscale size and high material quality [22]. Over the past decade, although many linear-mode NW-APDs have been reported [23][24][25][26][27][28][29][30][31][32], there is only one report on nanowire APDs operating above their breakdown voltage (i.e. NW-SPADs or Geiger-mode NW-APDs) [21], because of the stringent requirement in epitaxial growth and device fabrication of these types of nanowire devices.…”
Section: Introductionmentioning
confidence: 99%